The effects of adding exogenous lignocellulose degrading bacteria during straw incorporation in cold regions on degradation characteristics and soil indigenous bacteria communities - Wang, Yunlong; Zhang, Xuelian; Lou, Zixi; An, Xiaoya; Li, Xue; Jiang, Xinbo; Wang, Weidong; Zhao, Hongyan; Fu, Minjie; Cui, Zongjun (Frontiers in Microbiology, 2023)
Low temperature is one of the bottleneck factors that limits the degradation of straw during rice straw incorporation. Determining strategies to promote the efficient degradation of straw in cold regions has become a highly active research area. This study was to investigate the effect of rice straw incorporation by adding exogenous lignocellulose decomposition microbial consortiums at different soil depths in cold regions. The results showed that the lignocellulose was degraded the most efficiently during straw incorporation, which was in deep soil with the full addition of a high-temperature bacterial system. The predominant bacteria SJA-15, Gemmatimonadaceae, and Bradyrhizobium promoted straw degradation. The concentration of bacterial system and the depth of soil had significantly positive correlations on lignocellulose degradation. These results provide new insights and a theoretical basis for the changes in the soil microbial community and the application of lignocellulose-degrading composite microbial systems with straw incorporation in cold regions.